Clinical laboratory science: a profession with honors. - Hubbard JD; Sawyer B; Rice-Spearman L (Clinical Laboratory Science)
Texas Tech University Health Science Center (TTUHSC) supports a strong undergraduate honors program. Students are required to enter the Honors College as freshmen and enroll in at least 24 hours of honors-designated classes. Some of the clinical core courses in the clinical laboratory science (CLS) program are designated as honors courses so students can continue their contract agreement with the Honors College to enroll in at least six hours of honors credit at the junior and senior level. By providing further educational experiences out of class, these honors students are able to meet the requirements needed to graduate with highest honors. A CLS honors program not only benefits the student but also the faculty involved and the program curriculum.